Excipientes de medicamentos e as informações da bula - Balbani, Aracy Pereira Silveira (2006)
Aim: To evaluate the presence of preservatives, dyes, sweeteners and flavouring substances in 73 pharmaceutical preparations of 35 medicines for oral administration, according to drug labeling information about the excipients. Methods: 35 medications were selected, both over-the-counter and prescription durgs, marketed in Brazil. The sample included: analgesic/antipyretic, antimicrobial, mucoregulatory, cough and cold, decongestant, antihistamine, bronchodilator, corticosteroid, antiinflammatory and vitamin medications. We collected data on 73 preparations of these drugs, according to drug labeling information regarding preservatives, dyes, sweeteners and flavourings. Results: Methylparaben and propylparaben were the most common preservatives found (43% and 35.6% respectively). The most common sweeteners were: sucrose (sugar) (53.4%), sodium saccharin (38.3%) and sorbitol (36.9%). Twenty-one medicines (28,7%) contained two sweeteners. Colourless medicines predominated (43.8%), followed by those with sunset yellow dye (FD&C yellow no. 6) (15%). Five products (6.8%) contained more than one colour agent. Tartrazine (FD&C yellow no. 5) was present in seven preparations (9.5%). Fruit was the most common flavouring found (83%). Labelings of drugs which contained sugar frequently omitted its exact concentration (77%). Of the four labelings of medicines which contained aspartame, two did not warn patients regarding phenylketonuria. Conclusions: Omission and inacuracy of drug labeling information on pharmaceutical excipients may expose susceptible individuals to adverse reactions caused by preservatives and dyes. Complications of inadvertent intake of sugar-containing medicines by diabetics, or aspartame intake by patients with phenylketonuria may also occur.